An interpretation of proper name references based on “Principality of Existence” theory - Asadi, Siavash (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
One of the most important philosophical problems, at least in tradition of analytical philosophy, is the problem of proper names’ references. This paper intends to represent a new interpretation of the reference of proper names based on the theory of Principality of Existence developed by Mulla Sadra. He has mentioned the differences between nominal existence and infinitive existence. The latter is an abstract concept of being while nominal existence is the principal reality or the fact of things that has a real and a mental appearance. In Islamic Philosophy context we can consider the real appearance as essence (dhat) which is indeed special limitation of nominal existence and makes the entity of an existent like X. On the other hand mental appearance could be considered as quiddity (mahiyyah) which has an epistemic aspect re-presenter of essence. On this basis this paper argues that the proposition “X exists” could be turn to “nominal existence is X” and the nominal existence, as the unchangeable fact, would be the best alternative of a proper name’s reference. Also, changes on properties of an entity are caused by changes on limitations of existence without any on the reference of proper names.